2012
DOI: 10.1093/bja/aes332
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex in rocuronium anaphylaxis: dose matters

Abstract: This audit has inherent weakness including a small sample size and lack of a control group. However, this report highlights the advantages of ultrasound guidance in enhancing the accuracy and safety profile of a minimally neuro-destructive technique. Further randomized controlled trials are needed to confirm the efficacy of this treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 3 publications
1
25
0
6
Order By: Relevance
“…Sugammadex has been proposed as a useful treatment for anaphylaxis symptoms caused by rocuronium [59,60]. However, in a recently published series of cases, sugammadex did not modify the course of the reaction [61].…”
Section: Vasoactive Drugsmentioning
confidence: 98%
“…Sugammadex has been proposed as a useful treatment for anaphylaxis symptoms caused by rocuronium [59,60]. However, in a recently published series of cases, sugammadex did not modify the course of the reaction [61].…”
Section: Vasoactive Drugsmentioning
confidence: 98%
“…This more or less corresponds to the periods of time reported in clinical cases of rocuronium allergy in which an injection of sugammadex resulted in improved hemodynamic and/or respiratory status within a few minutes (Table). The case reported by Barthel et al 12 was a typical example of the need to inject a sufficient dose when firstly, a high dose of rocuronium has been used (0.8 mgÁkg -1 in this case), and also, the time to onset of allergic symptoms following the injection of rocuronium was immediate. This is also consistent with the case of Conte et al, 11 where the authors administered sugammadex 14 mgÁkg -1 six minutes after a dose of rocuronium 0.6 mgÁkg -1 , resulting in correction of the hypotension within approximately one minute.…”
mentioning
confidence: 75%
“…Similarly, what dose of sugammadex is suitable in this context? 12 Barthel et al 12 (Table) reported the case of a patient who suffered serious anaphylactic shock (grade III) following administration of rocuronium. The first dose of sugammadex (12 mgÁkg -1 ) allowed transient improvement of the hemodynamic status.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of case reports of rocuronium-induced anaphylaxis, where sugammadex administration, along with resuscitative efforts, has significantly improved clinical parameters and/or outcome. [128][129][130][131][132] Sugammadex may be a useful adjunct to managing rocuronium-induced anaphylaxis. 133,134 However, one cutaneous model disputes sugammadex use in this situation, warranting the need for further studies.…”
mentioning
confidence: 99%